2021
DOI: 10.3390/nu13030887
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration during Endurance Exercise: Challenges, Research, Options, Methods

Abstract: During endurance exercise, two problems arise from disturbed fluid–electrolyte balance: dehydration and overhydration. The former involves water and sodium losses in sweat and urine that are incompletely replaced, whereas the latter involves excessive consumption and retention of dilute fluids. When experienced at low levels, both dehydration and overhydration have minor or no performance effects and symptoms of illness, but when experienced at moderate-to-severe levels they degrade exercise performance and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 120 publications
(173 reference statements)
0
19
0
Order By: Relevance
“…There have been multiple studies looking at the optimal oral fluid replacement beverages. Studies in the sports medicine literature have compared different methods of oral hydration, and more than just sodium is required to achieve sufficient hydration (McCubbin et al, 2020;Armstrong, 2021). Rehydration solutions need 75 mM of glucose per liter of water for efficient intestinal absorption of sodium (Binder et al, 2014).…”
Section: Oral Hydration For Orthostatic Intolerancementioning
confidence: 99%
“…There have been multiple studies looking at the optimal oral fluid replacement beverages. Studies in the sports medicine literature have compared different methods of oral hydration, and more than just sodium is required to achieve sufficient hydration (McCubbin et al, 2020;Armstrong, 2021). Rehydration solutions need 75 mM of glucose per liter of water for efficient intestinal absorption of sodium (Binder et al, 2014).…”
Section: Oral Hydration For Orthostatic Intolerancementioning
confidence: 99%
“…Furthermore, high sodium or salt intake has also been linked with a high risk of cardiovascular diseases in the general population [4,5]. Studies have demonstrated that water and sodium deficits are predisposing factors for exertional heat stroke and exertional heat exhaustion [6]. Therefore, it is of vital importance to maintain the proper consumption of water and sodium for the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid intake during exercise is essential and must be considered before, during, and after exercise (Armstrong, 2021;Je´quier & Constant, 2010;Kenefick & Cheuvront, 2012;McDermott et al, 2017). For sports that are carried out for less than 60 minutes, the reduced fluid can be replaced with mineral water intake only (Je´quier & Constant, 2010;Porcari et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…For sports that are carried out for less than 60 minutes, the reduced fluid can be replaced with mineral water intake only (Je´quier & Constant, 2010;Porcari et al, 2015). If the exercise duration ranges from 60 -120 minutes, then mineral water alone is not enough, but an additional intake of electrolytes contained in sweat as metabolic waste is also required (Armstrong, 2021;Porcari et al, 2015), usually contained in milk (Amiri et al, 2019;Castro-Sepúlveda et al, 2016;Dow et al, 2019;Russo et al, 2019) and coconut water (Syafriani et al, 2014). After more than two hours of physical activity, in addition to water and electrolytes, it is also necessary to have an additional intake containing carbohydrates and protein, which are usually only found in milk.…”
Section: Resultsmentioning
confidence: 99%